Understanding the factors affecting the attraction and retention of health professionals in rural and remote areas: a mixed-method study in Niger - Belaid, Loubna (Hum Resour Health, 2017)
BACKGROUND: The critical shortage of human resources in health is a critical public health problem affecting most low- and middle-income countries, particularly in sub-Saharan Africa. In addition to the shortage of health professionals, attracting and retaining them in rural areas is a challenge. The objective of the study was to understand the factors that influence the attraction and retention of health professionals working in rural areas in Niger. METHODS: A mixed-method study was conducted in Tillabery region, Niger. A conceptual framework was used that included five dimensions. Three data collection methods were employed: in-depth interviews, documentary analysis, and concept mapping. In-depth interviews were conducted with three main actor groups: policy-makers and Ministry of Health officials (n = 15), health professionals (n = 102), and local health managers (n = 46). Concept mapping was conducted with midwifery students (n = 29). Multidimensional scaling and cluster analysis were performed to analyse the data from the concept mapping method. A content analysis was conducted for the qualitative data. RESULTS: The results of the study showed that the local environment, which includes living conditions (no electricity, lack of availability of schools), social factors (isolation, national and local insecurity), working conditions (workload), the lack of financial compensation, and individual factors (marital status, gender), influences the attraction and retention of health professionals to work in rural areas. Human resources policies do not adequately take into account the factors influencing the retention of rural health professionals. CONCLUSION: Intersectoral policies are needed to improve living conditions and public services in rural areas. The government should also take into account the feminization of the medical profession and the social and cultural norms related to marital status and population mobility when formulating human resources management policies.